Emi2 inhibition of the Anaphase-promoting Complex/Cyclosome absolutely requires Emi2 binding via the C-Terminal RL Tail - Ohe, Munemichi; Inoue, Daigo (Molecular biology of the cell, 2010)
Emi2 (also called Erp1) inhibits the anaphase-promoting complex/cyclosome (APC/C) and thereby causes metaphase II arrest in unfertilized vertebrate eggs. Both the D-box and the zinc-binding region (ZBR) of Emi2 have been implicated in APC/C inhibition. However, it is not well known how Emi2 interacts with and hence inhibits the APC/C. Here we show that Emi2 binds the APC/C via the C-terminal tail, termed here the RL tail. When expressed in Xenopus oocytes and egg extracts, Emi2 lacking the RL tail fails to interact with and inhibit the APC/C. The RL tail itself can directly bind to the APC/C, and, when added to egg extracts, either an excess of RL tail peptides or anti-RL tail peptide antibody can dissociate endogenous Emi2 from the APC/C, thus allowing APC/C activation. Furthermore, and importantly, the RL tail-mediated binding apparently promotes the inhibitory interactions of the D-box and the ZBR (of Emi2) with the APC/C. Finally, Emi1, a somatic paralog of Emi2, also has a functionally similar RL tail. We propose that the RL tail of Emi1/Emi2 serves as a docking site for the APC/C, thereby promoting the interaction and inhibition of the APC/C by the D-box and the ZBR.